variables affecting the structure of commercial advertising design (analytical study) (Al-Academy, 2024)
Design studies for commercial advertising constitute a living tributary of culture , because they represent reality and draw the dimensions of the future in order to confirm human tendencies from the various fields of life at whose doors commercial advertising knocks . through these tendencies , mental perceptions are revealed , whether negative or positive . The art of advertising represents the innovative aspect of the design process , and depends on the extent of the success of the advertising efforts undertaken by the advertising establishment , given that innovation is the heart of advertising , and that advertising is the innovative expression of new , creative ideas .